2019
DOI: 10.3389/fmolb.2019.00036
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Analysis of τRAMD Trajectories to Decipher Molecular Determinants of Drug-Target Residence Times

Abstract: Drug-target residence times can impact drug efficacy and safety, and are therefore increasingly being considered during lead optimization. For this purpose, computational methods to predict residence times, τ, for drug-like compounds and to derive structure-kinetic relationships are desirable. A challenge for approaches based on molecular dynamics (MD) simulation is the fact that drug residence times are typically orders of magnitude longer than computationally feasible simulation times. Therefore, enhanced sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 40 publications
1
78
0
Order By: Relevance
“…τRAMD was used to predict relative residence times for 70 HSP90 inhibitors (R 2 of 0.86 after removal of outliers) [266]. Analysis of inhibitor-protein contacts in the trajectories using machine learning improved residence time estimates and detected that interactions between a halogen or a methyl group in the loop-binder compounds with Phe138 lead to a longer residence time [269]. τRAMD was also recently applied to estimate relative residence times of ligands dissociating from different mutants of T4 lysozyme [270].…”
Section: Drug-protein Binding Kinetics Estimationmentioning
confidence: 99%
“…τRAMD was used to predict relative residence times for 70 HSP90 inhibitors (R 2 of 0.86 after removal of outliers) [266]. Analysis of inhibitor-protein contacts in the trajectories using machine learning improved residence time estimates and detected that interactions between a halogen or a methyl group in the loop-binder compounds with Phe138 lead to a longer residence time [269]. τRAMD was also recently applied to estimate relative residence times of ligands dissociating from different mutants of T4 lysozyme [270].…”
Section: Drug-protein Binding Kinetics Estimationmentioning
confidence: 99%
“…In additions, the prediction method was further tested by 94 HSP90 inhibitors. The results showed that the predicted R 2 of the 80 inhibitors was 0.75 with MAPE of 0.39 [11].…”
Section: Introductionmentioning
confidence: 97%
“…It is interesting to note that the pmf obtained by these simulations allowed a semi‐quantitative estimate of the energy barriers encountered by the ligands during their unbinding that well explains the different experimental ligand unbinding rates. Processing the RAMD trajectory and simulation unbinding times with a machine learning approach, Kokh et al were able to improve the correlation of the in‐silico ligand residence time with the experimental values for 70 and 94 inhibitors of heat shock protein 90 (HSP90) …”
Section: Methods To Compute Lpb Kineticsmentioning
confidence: 99%